SOCIAL CHANGES IN RURAL AREAS: INCOMES AND EXPENDITURES OF RURAL HOUSEHOLDS - Chmieliński, Paweł; Chmielewska, Barbara (Economics of Agriculture, 2018)
In the study we analyse changes in the level and structure of income and expenditure of households in rural and urban areas during the period of Polish integration with the European Union. This allows to answer the question of whether and how the social distance divides the residents of the rural and urban areas. The results showed improvement in economic and social situation in the rural areas. The living gap between rural residents and urban residents decreased. In the structure of incomes of rural households, the share of income from non-agricultural sources increased and at the same time the share of expenditure on food in total expenditure was smaller. However, the differences are still signifcant. The challenge for rural development policy is to reduce the gap between rural and urban areas, especially in terms of quality of life. This requires further development of non-agricultural jobs in rural areas.